PROFIL RUMAH TANGGA BURUH TANI DI KANAGARIAN UJUNG GADING KABUPATEN PASAMAN BARAT - Nurhidayati, Nurhidayati; Rianto, Slamet; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
Paddy Level produce will influence food pattern of a farm worker, because if level produce by paddy is high, so, paddy laborer will have many opportunity to work in another people field, like an education that can form a good nation and certain organizational to be more, but, because lack of the expense it can make someone cannot get an education. And because lack of economics by farm worker will affect to situation and condition of settlement of resident, so the consequence of this is cannot fulfill adequate health. If the family member much, so daily need will increase. The purpose of this research is to get data, information, and farm worker profile in Ujung Gading Sub-Province West Pasaman seen from : 1(food condition 2) education condition 3) earnings condition 4) health condition. Method of this research is descriptive research. And the population of this research is all head family of farm worker in Ujung Gading consists of 1020 head family. Sample of this Research taken by proposional random sampling. The proposition is about 20% so the sample of this research is about 79 head family. The data collection use a questionnaire and analyses data technique use percentage formula.Result of this research indicate some indicator 1) farm worker family ability in fulfilling need pertained good, Where frequency of eat every daily (1) enough for 24 people (30,4 %), (2) less 55 people (69,6 %), (3) not yet 0 people (0 %), (4) more than enough 0 people (0 %), 2) farm worker family ability to get education is average. Where (1) Senior High School graduated about 39 people (49,4%), (2) unfinish from Senior High School about 18 people (22,8%), (3) Junior High School graduated about 7 people (8,9%), (4) unfinish from Junior High School about 4 people ( 5%), (5) Elementary school graduated about 7 people (8,9%), (6) unfinish from Elementary school about 2 people (2,5%), (7) University graduated about 0 people (0%), (8) Unfinish from university about 2 people (2,5 3) farm worker earnings ability is average. Because the farm worker earning is above one million/month (1) more than 2.000.000 about 0 people (0%), (2) 1.100.000 until 1.900.000 about 40 people (50,6 %), (3) 900.000 until 1.000.000 about 28 people (35,4%) .(4) 500,000-800.000 about 11 people (14%), but their salary is uncertain ,there is daily salary, weekly salary and monthly 4) farm worker ability in reaching health is unfavourable. Because in this year some of laborer had some disease like fever and cold about 6 people ( 0,9%).